2014
DOI: 10.1016/j.bpj.2014.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Stress Inhibits Proliferation in Tumor Spheroids through a Volume Limitation

Abstract: In most instances, the growth of solid tumors occurs in constrained environments and requires a competition for space. A mechanical crosstalk can arise from this competition. In this article, we dissect the biomechanical sequence caused by a controlled compressive stress on multicellular spheroids (MCSs) used as a tumor model system. On timescales of minutes, we show that a compressive stress causes a reduction of the MCS volume, linked to a reduction of the cell volume in the core of the MCS. On timescales of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
255
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(298 citation statements)
references
References 34 publications
33
255
2
Order By: Relevance
“…This finding is consistent with the view of the late G1 checkpoint as an integrator of numerous stresses, including osmotic, chemical and heat shock stresses [36][37][38]. Force-induced cell cycle arrest has been observed in mammalian cells [39,40], but the associated mechanical stresses are two to three orders lower than the stalling pressure measured in our experiments.…”
supporting
confidence: 93%
“…This finding is consistent with the view of the late G1 checkpoint as an integrator of numerous stresses, including osmotic, chemical and heat shock stresses [36][37][38]. Force-induced cell cycle arrest has been observed in mammalian cells [39,40], but the associated mechanical stresses are two to three orders lower than the stalling pressure measured in our experiments.…”
supporting
confidence: 93%
“…Both the simulation and the clinical results were consistent with each other. These results were also confirmed and proved by previous studies that showed that the inhomogeneous environment could influence tumor proliferation and invasion through compressive stress [42][43][44]70]. The most common metastasis site for breast cancer is bone (48%), followed by lung (26%), liver (30%) and brain (7%) [6][7][8].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, we speculated that a percolation cluster with a different occupation probability should be suitable for describing the proliferation and spread of a tumor in an inhomogeneous surrounding matrix, which itself should be compressive to tumor proliferation and invasion. The results are basically in accordance with previous studies that showed that the surrounding matrix possesses a specific external pressure on a solid tumor [42][43][44]70]. …”
Section: Influence Of Tissue Inhomogeneity On Tumor Proliferation Andsupporting
confidence: 92%
See 1 more Smart Citation
“…The same mechanism could explain different growth speeds in expanding one-cell thick dense monolayers observed by Bru et al [90], and growth saturation of multicellular spheroids in agarose gel [62,82,144] observed by Helmlinger et al [11], and Galle et al [153]. Recently Delarue et al [154] confirmed inhibition of proliferation in tumor spheroids by compressive stress.…”
Section: Achievements Limitations and Practical Usementioning
confidence: 73%